CEO Tenure Dan Earnings Management: Peran Female On Boards Dan Komisaris Independen Sebagai Variabel Moderasi(Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022) - Nurul Azkiah; Alfiati Silfi; Rezi Abdurrahman (Jurnal IAKP : Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2025)
The purpose of this study to examine the effect of CEO tenure on earnings management with female on boards and independent commissioners as moderating variables in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Earnings management is measured using discretionary accruals, calculated using the Modified Jones Model, which reflects the degree of earnings manipulation. CEO tenure is measured by the number of years the CEO has served in the company. Female on boards is measured by the percentage of female members on the board of directors, and independent commissioners are measured by the percentage of independent commissioners on the board. The sample consists of 131 manufacturing companies selected using purposive sampling, resulting in 655 data points over five years. Data analysis was conducted using WarpPLS 8.0. The results show that CEO tenure has a significant negative effect on earnings management. Female on boards positively moderates this relationship, while independent commissioners do not. Control variables, such as profitability and leverage, significantly affect earnings management. However, company size and the number of board members do not have a significant effect.